Flux densities of meteoroids derived from optical double-station observations. (1st September 2017) - Koschny, D.; Drolshagen, E.; Drolshagen, S.; Kretschmer, J.; Ott, T.; Drolshagen, G.; Poppe, B.
Abstract: We have developed a new method to determine flux densities of meteoroids using optical double-station meteor observations. It is based on the assumption that the velocity distribution is constant for all mass bins. By comparing the observed velocity distribution with a model distribution we determine de-biasing factors to correct for meteors too slow to emit a detectable amount of light. We use this method to correct a dataset of about 20000 double-station meteoroids detected over a period of about 3.5 years with the Canary Island Long-Baseline Observatory (CILBO). The resulting cumulative flux density has a slope comparable to the model of Grün et al. (1985). The largest uncertainty is the luminous efficiency. Depending on which values for the luminous efficiency are assumed, the mass estimate deviates by about one to 1.5 orders of magnitude. Using the luminous efficiencies derived by Weryk et al. (2013) results in an excellent agreement of our data with the Grün data. Highlights: We present a novel method to determine meteoroid flux densities from optical meteor observations. The results are in excellent agreement with data from Gruen (1985).